Dr. Ruth A. Parmelee and the Changing Roll of Near East Missionaries in Early Twentieth Century Turkey - Metaxas, Virginia (Role of the American Board in the World: Bicentennial Reflections on the Organization's Missionary Work, 1810-2010, 2012)
The American Board of Commissioners for Foreign Missions (ABCFM) was the country's first creator of overseas Christian missions. Founded in 1810 and supported by a coalition of Calvinist denominations, the ABCFM established the first American missions in India, China, Africa, Oceania, the Middle East, and many other places. It was America's largest missionary organization in the nineteenth century, and its influence was immense. Its missionaries established the first Western schools and hospitals in many parts of the world, and they successfully promoted women's rights and other ideals from the Enlightenment. They also transformed oral languages such as Zulu, Hawaiian, and Cherokee into written form, and they preserved many elements of premodern cultures (albeit not always intentionally). The contributors to this book provide valuable insights on the work of the ABCFM (which exists today under a different name). Some of the contributors profile the lives of notable ABCFM missionaries, others focus on ideological shifts within the Board, and still others chronicle the Board's role in historic events, including the Opium Wars, the colonization of Hawai'i, and the Armenian Genocide. From reading this book, people will come to understand why the ABCFM is widely viewed as America's most historically significant missionary organization.
Keywords: American Board of Commissioners for Foreign Missions; History; Congregational churches; Missions; Missions, American; dept.his; faculty_collection